Mechanics and rates of tidal inlet migration: Modeling and application to natural examples. Issue 11 (10th November 2016) - Nienhuis, Jaap H.; Ashton, Andrew D.
Abstract: Tidal inlets on barrier coasts can migrate alongshore hundreds of meters per year, often presenting great management and engineering challenges. Here we perform model experiments with migrating tidal inlets in Delft3D‐SWAN to investigate the mechanics and rates of inlet migration. Model experiments with obliquely approaching waves suggest that tidal inlet migration occurs due to three mechanisms: (1) littoral sediment deposition along the updrift inlet bank, (2) wave‐driven sediment transport preferentially eroding the downdrift bank of the inlet, and (3) flood‐tide‐driven flow preferentially cutting along the downdrift inlet bank because it is less obstructed by flood‐tidal delta deposits. To quantify tidal inlet migration, we propose and apply a simple mass balance framework of sediment fluxes around inlets that includes alongshore sediment bypassing and flood‐tidal delta deposition. In model experiments, both updrift littoral sediment and the eroded downdrift inlet bank are sediment sources to the growing updrift barrier and the flood‐tidal delta, such that tidal inlets can be net sink of up to 150% of the littoral sediment flux. Our mass balance framework demonstrates how, with flood‐tidal deltas acting as a littoral sediment sink, migrating tidal inlets can drive erosion of the downdrift barrier beach. Parameterizing model experiments, we propose a predictive model of tidal inlet migration rates based upon the relative momentum flux of the inlet jet and the alongshore radiation stress; we then compare these predicted migration rates to 22 natural tidal inlets along the U.S. East Coast and find good agreement. Key Points: Tidal inlet migration rate depends on alongshore sediment bypassing and flood‐tidal delta deposition We parameterize Delft3D‐SWAN model experiments to predict tidal inlet migration rates We compared migration prediction to 57 (22 unaltered) inlets along the U.S. coastline and find good agreement